1997
DOI: 10.1017/s0020743800064138
|View full text |Cite
|
Sign up to set email alerts
|

Neo-Tribalism in Iraq: Saddam Hussein's Tribal Policies 1991–96

Abstract: The intention of this article is to show that, when applying his tribal policies, Saddam Hussein altered the Baʿth Party's most central tenets of faith, how and why he did this, and what it meant for Iraqi society and for the ruling party. Saddam Hussein's tribal policy started soon after the party came to power in July 1968, but it went through a quantum leap in the late 1980s and the early 1990s. First, rather than eliminating the tribal shaykh as a sociopolitical power, as dictated by party doctrine, he end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(24 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…The latter combined those policies with a concurrent plan to destroy and reconstruct Kurdish identity as a manifestation of tribalism. Rather than eradicating ‘tribal sheykhs’, Saddam manipulated and controlled the sheykhs through Baathification policies in all of Iraq (Baram : 1). He also tribalized his own Ba’ath party, as well as the Iraqi army, and extended a ‘tribal sense of loyalty’ (imagined or real) to its rule, even referring to the Ba’ath Party as ‘the tribe’.…”
Section: The Tribal Kurdistan and The Perpetuation Of Internal Colomentioning
confidence: 99%
“…The latter combined those policies with a concurrent plan to destroy and reconstruct Kurdish identity as a manifestation of tribalism. Rather than eradicating ‘tribal sheykhs’, Saddam manipulated and controlled the sheykhs through Baathification policies in all of Iraq (Baram : 1). He also tribalized his own Ba’ath party, as well as the Iraqi army, and extended a ‘tribal sense of loyalty’ (imagined or real) to its rule, even referring to the Ba’ath Party as ‘the tribe’.…”
Section: The Tribal Kurdistan and The Perpetuation Of Internal Colomentioning
confidence: 99%
“…Khoury in particular picks up on the theme of the fraying of the Ba'th institutional apparatus that had been identified following the disaster of 1991. Khoury critiques much of the literature of the 1990s concerning Saddam's alleged turn to “neo‐tribalism” (Baram, ; Dawisha, ; Jabar, ). Instead, Khoury argues that the regime had always been characterized by improvisation and a kind of ideological and practical mélange in which violence was often justified by the desire for development and national improvement.…”
Section: Fall Of the Dictator Rise Of Social Science?mentioning
confidence: 99%
“…He had concluded that he needed to risk entering conflict to demonstrate his courage and to affirm his claim to pan-Arab and Islamic leadership as well as to traditional Arab values of manly valor (al-futuwwa, al-muruwwa) and honor (al-sharaf). 13 Saddam expected a massive air campaign and planned to survive it. In the succeeding ground campaign, he hoped to engage the U.S. "Vietnam complex."…”
Section: Why Saddam Did Not Withdraw From Kuwaitmentioning
confidence: 99%